Improving Start up Performance of Single Speed Compressors by Stator Winding Design: An Advance Study - Tugba Cetinturk (Advanced Aspects of Engineering Research Vol. 11, 2021)
Some east countries have line voltage fluctuations and voltage drops which can cause cooling problems on refrigerators because compressors cannot start up at these low line voltages. That’s why not only COP[1], but also start up performance at low voltages is critical on single speed compressors. Torque-speed curves of single speed asynchronous motors are so critical for compressor start up performance which takes form by motor design. Depending on compressor mechanical efficiency and shaft power needed, the asynchronous motor winding design should be fine-tuned and torque speed curve should be adjusted for start up properly at low voltage values. Even when the start torque at 0 rpm and breakdown torque values are high enough to provide low voltage compressor starting, instant torque decreases along the curve negatively effects start up performance. Start winding distribution has a remarkable effect on compressor start up performance. This study analyses torque-speed curve characteristics of asynchronous motors and determines stator winding design methods to improve compressor start up performance. The findings are also validated with motor and compressor test results. [1]COP: Acronym of Coefficient of Performance, which is ratio of compressor cooling capacity to input power at steady state working condition.